Military aircraft, origins to 1918 an illustrated history of their impact - Murphy, Justin D. (ABC-CLIO, 2005)
Military Aircraft, Origins to 1918: An Illustrated History of Their Impact is a detailed, authoritative exploration of the role and development of military aviation, from its beginnings to the conclusion of World War I. Military history scholar Justin Murphy carefully illustrates the impact of aircraft on military warfare, examines the different types of aircraft, and includes a wealth of photographs and descriptions. Organized thematically, the work covers everything from the origins of military aviation and the impact of aircraft on World War I to the role of reconnaissance missions, auxiliary aircraft, fighters, and bombers. Each chapter highlights key individuals, advancements in aviation technology, industrial organization and aircraft production, and the influence of aircraft on military tactics and strategy. Murphy also demonstrates how aircraft contributed to the development of total war and blurred the lines that had traditionally separated combatants and noncombatants.